DYOTHELITISME DALAM PERSPEKTIF JOHN CALVIN: ANALISIS THEOLOGIS TERHADAP KONSEP DUALITAS KEHENDAK KRISTUS - Mozes Lawalata (Manna Rafflesia, 2025)
Dyothelitism is the doctrine that teaches that in Christ there are two different wills, the divine will and the human will. History records that this doctrine has sparked a very long theological debate among Christians, especially between the Monophysites and the Nestorians. Starting from this fact, through this article, the author will analyse the doctrine of dyothelitism in the perspective of John Calvin, namely analysing how Calvin interpreted and integrated the two wills of Christ in the Christological framework he built, as well as its doctrinal implications for the church today. This research uses a qualitative method with a historical-theological approach, referring to Calvin's works, especially Institutio Christianae Religionis, as well as the results of the Council of Constantinople III (681 AD) which confirmed Dyothelitism as an orthodox doctrine. The analysis shows that the duality of Christ's will not only maintains the balance between His divine and human natures, but also has a significant impact on the understanding of Christian soteriology and spirituality. The article also shows that dyothelitism not only maintains the integrity of Christ's nature as both God and man, but also ensures the effectiveness of His work of salvation. By understanding this concept, the church can more fully appreciate the mystery of the Incarnation and the redemptive work of Christ.